Analisis atas Penghitungan Penghasilan Kena Pajak sebagai Dasar Penetuan Besarnya Pajak Penghasilan (PPh) Terutang Studi Kasus PT PQR - Eliza, Eliza; Clara Monica, Gracia; Dariansyah, Deddy (Politeknik Negeri Jakarta, 2024)
This study discusses the analysis of calculating taxable income as the basis for determining the income tax payable by PT. PQR. The methode used in this study is the method of descriptive analytical with data collection technique using literature studies (Library Research) and field studies (Field Research). The result of this study is that the calculation of taxable income carried out by the company is not fully in accordance with the provisions of tax laws and regulations due to the lack of competent human resources and understanding of the provisions of the tax laws and regulations. Companies are advised to improve the quality and quantity of human resource to be more competent in implementing the provisions of the tax laws and regulations. Keywords : Commercial dan Fiscal Financial Reports, Fiscal Corrections, Taxable income, Income Tax Payable